Sensitivity Analysis of a Bioinspired Refractive Index Based Gas Sensor - Gao, Yang; Xia, Qi; Liao, Guanglan; Shi, Tielin (Journal of bionics engineering, 2011)
It was found out that the change of refractive index of ambient gas can lead to obvious change of the color of Morpho butterfly＇s wing. Such phenomenon has been employed as a sensing principle for detecting gas. In the present study, Rigorous Coupled-Wave Analysis （RCWA） was described briefly, and the partial derivative of optical reflection efficiency with respect to the refractive index of ambient gas, i.e., sensitivity of the sensor, was derived based on RCWA. A bioinspired grating model was constructed by mimicking the nanostructure on the ground scale of Morpho didius butterfly＇s wing. The analytical sensitivity was verified and the effect of the grating shape on the reflection spectra and its sensitivity were discussed. The results show that by tuning shape parameters of the grating, we can obtain desired reflection spectra and sensitivity, which can be applied to the design of the bioinspired refractive index based gas sensor.